• 2022-06-09
    曲线\( y = 3{x^4} - 4{x^3} + 1 \)的凹、凸的区间为( ) 。
    A: 在\( ( - \infty ,{2 \over 3}], \) \( [1, + \infty ) \)内为凸,\( [{2 \over 3},1] \)内为凹
    B: 在\( ( - \infty ,0] \)内为凹,\( [0,{2 \over 3}] \)内为凸
    C: 在\( ( - \infty ,0] \)内为凸,\( [{2 \over 3}, + \infty ) \)内为凹
    D: 在\( ( - \infty ,0], \)\( [{2 \over 3}, + \infty ) \)内为凹,\( [0,{2 \over 3}] \)内为凸
  • D

    举一反三

    内容

    • 0

      将\(f(x) = {1 \over {2 - x}}\)展开成\(x \)的幂级数为( )。 A: \({1 \over {2 - x}} = \sum\limits_{n = 0}^\infty { { { { x^n}} \over { { 2^{n }}}}} \),\(( - 2,2)\) B: \({1 \over {2 - x}} = \sum\limits_{n = 0}^\infty { { { { x^n}} \over { { 2^{n }}}}} \),\(\left( { - 2,2} \right]\) C: \({1 \over {2 - x}} = \sum\limits_{n = 0}^\infty { { { { x^n}} \over { { 2^{n + 1}}}}} \),\(( - 2,2)\) D: \({1 \over {2 - x}} = \sum\limits_{n = 0}^\infty { { { { x^n}} \over { { 2^{n + 1}}}}} \),\(\left( { - 2,2} \right]\)

    • 1

      将\(f(x) = {1 \over {1 + {x^2}}}\)展开成\(x\)的幂级数为( )。 A: \({1 \over {1 + {x^2}}} = \sum\limits_{n = 0}^\infty { { {( - 1)}^n}{x^{2n}}} \matrix{ {} & {} \cr } ( - \infty < x < + \infty )\) B: \({1 \over {1 + {x^2}}} = \sum\limits_{n = 0}^\infty { { {( - 1)}^n}{x^{2n}}} \matrix{ {} & {} \cr } ( - 1< x < 1)\) C: \({1 \over {1 + {x^2}}} = \sum\limits_{n = 0}^\infty { { {( - 1)}^n}{x^{2n}}} \matrix{ {} & {} \cr } ( - 1 < x < 1)\) D: \({1 \over {1 + {x^2}}} = \sum\limits_{n = 0}^\infty { { x^{2n}}} \matrix{ {} & {} \cr } ( - 1 < x < 1)\)

    • 2

      下列广义积分收敛的是( )。 A: \( \int_1^{ + \infty } { { x^{ - 3}}dx} \) B: \( \int_1^{ + \infty } { { 1 \over {\sqrt x }}dx} \) C: \( \int_0^{ + \infty } {\cos xdx} \) D: \( \int_0^2 { { 1 \over { { {(1 - x)}^2}}}dx} \)

    • 3

      函数$f(x)=x^3-5x^2-8x$的上凸区间为 A: $(-\infty,\frac{5}{3}) $ B: $(\frac{5}{3},+\infty) $ C: $(-\infty,-\frac{5}{3}) $ D: $(-\frac{5}{3},+\infty) $

    • 4

      将函数\(f(x) = {e^x}\)展开成\(x\)的幂级数为( )。 A: \({e^x} = \sum\limits_{n = 0}^\infty { { { { x^n}} \over {n!}}} ( - \infty < x < + \infty )\) B: \({e^x} = \sum\limits_{n = 0}^\infty { { {( - 1)}^n} { { {x^n}} \over {n!}}} ( - \infty < x < + \infty )\) C: \({e^x} = \sum\limits_{n = 0}^\infty { { { { x^n}} \over {n!}}} ( - 1 < x < 1)\) D: \({e^x} = \sum\limits_{n = 0}^\infty { { {( - 1)}^n} { { {x^n}} \over {n!}}} ( - 1 < x < 1)\)